Sun-powered solutions: Investigating productivity and economics of small-scale solar desalination system - Ahmad Manasrah; Mai Bani Younes; Eman Abdelhafez (Case Studies in Thermal Engineering)
Freshwater demand is one of the most critical challenges facing many countries in the world. Jordan is a country in the middle east that is considered one of the poorest countries for renewable freshwater supplies in the world. Though desalination may be one of the solutions to the problem, the cost and energy expenses could be an obstruction. However, with an abundance of annual solar irradiance in Jordan, solar desalination systems, particularly small-scale ones, are considered better alternatives. In this study, a residential-scale solar desalination system is investigated. The design includes evacuated-tube solar heaters with a heat pipe, and flashing units comprising three desalination stages. The experiments included single-stage, double-stage, and triple-stage desalination. The results showed that production rates of 2.2 kg/m2 using single-stage, 4.7 kg/m2 using double-stage, and 6.4 kg/m2 using triple-stage desalination were obtained from the system. The solar water heater used in the system exhibited an average thermal efficiency of 73 %. The economic analysis revealed that the payback period for the triple-stage desalination system is 8 years. The annualized rate of return was calculated to be 2.2 %, assuming the system operates for 4 h per day and 300 days per year.